Innovation of Calibrated Dk Drape for Quantitative Measurement of Blood Loss During and Immediately After Vaginal Delivery (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Postpartum Hemorrhage (PPH), a major cause of maternal mortality, is often diagnosed late. For early and proper diagnosis of PPH, blood loss has to be measured quantitatively during & after vaginal delivery.Objective: To prepare a low-cost, easy to make and easy to use transparent calibrated drape innovatively which may be used for quantitative measurement of blood loss; to explore its safety, efficacy and usability; and to find out satisfaction of mothers and service providers.Method: The study was done in three phases in Ashulia Women & Children Hospital and Institute of Women & Children Health (IWCH). First: an innovative approach was undertaken to develop a simple low-cost calibrated drape to measure blood loss during third stage of labour and immediately after delivery. A cross-sectional study was carried out on 40 mothers from 1st November 2023 to 30th April 2024 who delivered normally to find out the safety, efficacy and applicability of the drape in the second phase. To find out the level of satisfaction on using this newly innovated drape, a qualitative study was conducted on 40 mothers and 20 service providers in the third phase. Ethical clearance was obtained from IWCH.Results: A calibrated drape Dhaka (Dk) drape is made with thin transparent polythene shopping bags available in the market (capacity 12-15kg). One of the lateral sides of the bag is split open and refolded to give it a conical shape. It is calibrated at 300, 500 and 1000ml using simple technique first and then with marked scale. The device has a cone, a shorter and a longer side. The longer and wider side is spread under the buttock of the women (who is lying on the delivery table in a dorsal position with her buttock at the edge of the table), after the delivery of the baby and before the delivery of the placenta and kept there till the amount of bleeding is controlled/ reasonably low or for one hour. The swabs/gauze pieces used for any other bleeding such as repair of tear or episiotomy wound are to be weighed and added to the total blood loss. The drape is disposed of like other contaminated medical waste. Initially, the Dk drape is successfully used on 40 mothers during their vaginal delivery. The calculated cost of making the drape is only around Bangladesh Taka six (USD 0.05). According to the opinion of the patient and service providers the Dk drape is effective (correctly measuring blood loss), safe (no side effect or inconvenience), feasible (ease and willingness to use), accessible for regular use (availability). Conclusion: The Dk drape found to be an effective, low cost, safe, easy to make device to measure blood loss accurately during and immediately after vaginal delivery and early identification of and action for PPH, without the need for manufacturing and supply. It is easy to be used by the health service providers and acceptable to women and is safe.Recommendation: Due to its efficacy, low cost, safety, ease to make and use; and satisfaction of the patients and service providers; the calibrated Dk drape is recommended to be used after every vaginal delivery for quantitative measurement of blood loss accurately and easily.Bangladesh J Obstet Gynaecol, 2024; Vol. 39(2): 65-73